Workshop: Management of infertile couple - Zainuddin, Ahmad Murad; Ramli, Roszaman; Abdul Wahab, Azantee Yazmie (2010)
‘Management of Infertile Couple Workshop’ was held on the 30th April 2010 at Level 4, Medicine Building, IIUM Indera Mahkota Campus. The workshop was fully sponsored by Merck Serono. There were 26 participants: clinicians (21), nurses (3) and radiographers (2) from government and private hospitals or clinics around East Coast of Malaysia. The objectives of this programme are to educate and expose participants on basic infertile investigation, identify infertility problem, monitoring the patients using ultrasound guidance and know the basic semen analysis and sperm preparation.